Preparation of silicalite–polyamide composite membranes for desalination - Li, D.; He, L.; Dong, Dehua; Forsyth, M.; Wang, H. (John Wiley & Sons, Ltd, 2012)
Silicalite–polyamide composite membranes were synthesized via interfacial polymerization on a commercial polysulfone substrate, for the purpose of studying the effect of the addition of silicalite nanocrystals on the desalination property of polyamide membrane. The scanning electron microscopy (SEM) images showed that both plain polyamide membrane and silicalite–polyamide composite membranes exhibited rough surface morphology which is similar to the commercial polyamide membranes. The existence of silicalite nanocrystals in the silicalite–polyamide composite membrane was confirmed by energy dispersive X-ray spectroscopy (EDXS) and high-resolution transmission electron microscopy (HRTEM). The effect of loading of silicalite nanocrystals on the desalination property of membranes was examined. By increasing the loading of silicalite nanocrystals, the water flux of silicalite–polyamide composite membranes increased, whereas the salt selectivity decreased significantly. Plain polyamide membrane had salt rejection of 98.1% and a flux of 5.07 × 10−7 m3/m2·s, whereas the silicalite–polyamide composite membrane, prepared from trimesoyl chloride (TMC)–hexane with 0.5% (w/v) silicalite, had a water flux of 2.74 × 10−6 m3/m2·s and NaCl rejection of 50% at a feed pressure of 34.48 bar by using 2000 ppm salt solution as the feed. The transport mechanisms of the silicalite–polyamide composite membranes were discussed.